2008
DOI: 10.1007/s11664-007-0365-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of n-ZnO/p-Si Heterojunction Diodes Grown by Pulsed Laser Deposition at Different Oxygen Pressures

Abstract: Heterojunction diodes of n-type ZnO/p-type silicon (100) were fabricated by pulsed laser deposition of ZnO films on p-Si substrates in oxygen ambient at different pressures. These heterojunctions were found to be rectifying with a maximum forward-to-reverse current ratio of about 1,000 in the applied voltage range of -5 V to +5 V. The turn-on voltage of the heterojunctions was found to depend on the ambient oxygen pressure during the growth of the ZnO film. The current density-voltage characteristics and the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…Thus the junction was found to be rectifying and the turn-on voltage is about 1.5 V. The maximum forward-to-reverse current ratio was found to be about 15. This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions.…”
Section: I-v Characteristicscontrasting
confidence: 54%
See 2 more Smart Citations
“…Thus the junction was found to be rectifying and the turn-on voltage is about 1.5 V. The maximum forward-to-reverse current ratio was found to be about 15. This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions.…”
Section: I-v Characteristicscontrasting
confidence: 54%
“…This is on the lower side of that normally reported 6,19 . While Basu et al 6 have reported a forward to reverse current ratio of 80 at 1 V; Ajimsha et al 19 reported a value of 1000 at 5 V for n-ZnO/p-Si heterojunctions. Basu et al 6 deposited ZnO films on p-Si substrate by chemical vapor deposition (CVD) technique and Ajimsha et al 19 prepared ZnO films by pulsed LASER deposition technique.…”
Section: I-v Characteristicscontrasting
confidence: 54%
See 1 more Smart Citation
“…They reported several difficulties caused specially by the large lattice mismatch between Si and the ZnO layer and the formation of amorphous SiOx layers [17]. Ajimsha et al [18] reported the electrical characteristics of n-ZnO/p-Si heterojunction diodes grown by PLD at different oxygen pressures. Kumar et al [19] characterized sol-gel derived yttrium-doped n-ZnO/p-Si heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…However, such reports are still very limited. [15][16][17][18][19][20][21][22][23][24] In this work, n-ZnO/p-Si heterojunctions were constructed, in which the n-ZnO film served as an UV absorber, and Si as a visible and near-infrared absorber. The photogenerated carriers are separated at the n-ZnO/p-Si interface.…”
Section: Introductionmentioning
confidence: 99%